Improving Social Climate In Youth Detention - Trotter, Chris (International journal of offender therapy and comparative criminology, 2024)
Ongoing concerns have been expressed about the poor rehabilitative climate of youth detention centers, with a number of government inquiries examining the nature of the centers and how to improve their rehabilitative culture. Emerging research points to staff training and support as mechanisms to improve institutional climate. This study examines the impact on institutional climate of training and coaching staff in effective practice skills. Staff and young people, across three Australian detention centers, were administered a validated social climate measure prior to and 3 to 6 months following training and coaching. The social climate improved at a statistically significant level for staff. For young people the social climate improved but the improvement was not statistically significant. The measure was also administered at two control sites for staff where minimal changes in social climate were seen, suggesting that the staff improvements flowed from the training and coaching rather than from other organizational factors. It is concluded that training and coaching improved detention center social climate for staff although the study does not provide evidence that it improved significantly for young people.